An alternative measure of Standard of Living : The Body Mass Index in Colombia (2011)
This paper assesses the standard of living using health-relatedoutcomes instead of income-based measures. We use the Body Mass Index (BMI) as a categorical variable to take into account how far people are from a normal range associated to a desirable quality of life. This is a proxy of the Standard of Living Index for the Colombian case. An OrderedProbitModel is used to determine the probability of being within that normal range or not, with two different specifications: the normative one that takes into account the traditional categories in which the BMI is ranked,and the relative one, in which the distribution of the sample is incorporated. We found that education and a constructed index of living conditions have a significant effect on the dependent variable and that there are non-linear effects. We also found that people with walking difficulties and adults have less probability of having a normal BMI.